ANALISIS FITUR APLIKASI INTERNET MOVIE DATABASE (IMDB) DENGAN METODE CUSTOMER KNOWLEDEGE MANAGEMENT(CKM) - nathanael, audi; Nantu , Gregorius; Kristianto , Ryan Putranda (Jurnal Nasional Teknologi Komputer, 2023)
This study aims to analyze the features of the Internet Movie Database (IMDb) application using the Customer Knowledge Management (CKM) method. CKM is an approach to collecting, managing and leveraging customer knowledge to support decision making and improve customer relationships. In the context of IMDb, CKM can assist in understanding user needs and preferences, providing a better experience, and increasing user satisfaction. This study uses a feature analysis approach to evaluate key features in IMDb applications and determine how these features contribute to management. customer knowledge. Features that will be analyzed include complete information about movies and TV series, cast lists, directors, producers, ratings, user reviews, search features, recommendations, and community features. The method used in this study is CKM, which involves collecting data from different sources, such as IMDb application documentation, analysis of application components, and user feedback. These data are then analyzed and evaluated to determine the effectiveness of IMDb features in supporting customer knowledge management. The results of this analysis are expected to provide useful insights for IMDb application developers to improve user experience, improve existing features, and identify areas for improvement. potential. In addition, this research can also contribute to the understanding of the application of CKM in the context of the entertainment industry and the importance of customer knowledge management in achieving higher user satisfaction.